Perceptions of Johannesburg small business operators about their small business support systems - F. G. Netswera (South African Journal of Business Management, 2001)
Central to the current South African economic debates are the Issues of equity, black empowerment and the promotion of small business activities. The promotion of small business activities is felt relevant as they are assumed to be addressing most of the country's unemployment problem and those mentioned above while contributing largely to the GDP. Assumed problems facing this industry include the unavailability of support systems. This quantitative research explored through telephonic interviews, the perceptions of 60 Johannesburg small business operators of their small business support systems. The findings revealed access to information to be the perceived most important support system and business partnerships and subcontracting the least accessible.
Keywords: 650